(untitled) (Journal of Contemporary Studies, 2025)
Warfare has been a consistently evolving phenomenon, and kept transforming according to the dictates of prevalent combat environments, shaped by the global political, economic, technological and strategic dynamics. Consequently, warfare has morphed from conventionally waged large scale conflicts to modern-day hybrid, asymmetric and mostly grey zone battles, where it is hard to differentiate between war and peace. Evaluation of combat modes dictates revolution in the response methodologies as well, and thus realignment of strategy, resources and orientation becomes inevitable. A state’s entire national security hierarchy, especially a vital stakeholder like the intelligence, would need to decisively adapt for the impending challenges, mainly transpiring in the unconventional modes. Notwithstanding consistent revolution in the military affairs, there has not been compatible reforms undertaken to transform intelligence beyond conventionally oriented structures and functional modalities. This paper contends that national security intelligence has to evolve in compatibility with the changing modes of modern warfare.